In Vitro Correction of a Pseudoexon‐Generating Deep Intronic Mutation in LGMD2A by Antisense Oligonucleotides and Modified Small Nuclear RNAs. Issue 10 (7th August 2013) - Blázquez, Lorea; Aiastui, Ana; Goicoechea, Maria; Martins de Araujo, Mafalda; Avril, Aurélie; Beley, Cyriaque; García, Luis; Valcárcel, Juan; Fortes, Puri; López de Munain, Adolfo
<x xml:space="preserve">Abstract</x> c.1782+1072G>C mutation is the first deep‐intronic mutation in the CAPN3 gene, which leads to LGMD2A. The mutation causes the inclusion of a pseudoexon in mature CAPN3 mRNA. In this work, we demonstrate mutation pathogenicity with a minigene assay and we induce splicing modulation with Antisense Oligonucleotides (AONs) and modified U‐snRNAs. In addition, AON treatment restores correct splicing in fibroblasts from a LGMD2A patient which harbors this mutation. Our results indicate that SRSF1 splicing factor is involved in pseudoexon activation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>